2017
DOI: 10.3390/polym9020042
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Poly(ε-caprolactone) in Poly(vinylidene fluoride)/Poly(ε-caprolactone) Blend

Abstract: Abstract:The crystallization behavior of poly(ε-caprolactone) (PCL) in a poly(vinylidene fluoride) (PVDF)/PCL blend as well as on a highly orientated PVDF substrate was studied by means of POM, DSC and TEM. The results show that the miscibility of the PVDF/PCL blend and the spherulitic morphology of PVDF varies with the blend ratio. For all the compositions, the pre-existing PVDF crystals accelerated the crystallization of PCL because the PVDF exhibits very strong nucleation ability toward PCL as reflected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…It is well known that the PVDF crystals have three different molecular conformations: transgauche-trans-gauche′ (TGTG'), trans-trans-trans (TTT), trans-trans-trans-gauche (TTTG), and five different polymorphs: α (phase II), β (phase I), γ (phase III), δ, and ε [15,21]. Each of the polymorphs possess its unique properties which could affect the morphology and performance of the fabricated membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the PVDF crystals have three different molecular conformations: transgauche-trans-gauche′ (TGTG'), trans-trans-trans (TTT), trans-trans-trans-gauche (TTTG), and five different polymorphs: α (phase II), β (phase I), γ (phase III), δ, and ε [15,21]. Each of the polymorphs possess its unique properties which could affect the morphology and performance of the fabricated membrane.…”
Section: Resultsmentioning
confidence: 99%
“…These additives often show specific interactions with one of the other three components. Indeed, a number of publications focused on composited PVDF membranes has been published during the last decade [4,[13][14][15][16]. However, new methods and strategies have been applied for the PVDF polymers production, which could impact their polymorphs [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…giving rise again to a transcrystalline PCL layer. The nucleation effect of PVDF on PCL could also be detected by non-isothermal differential scanning calorimetry, as a meaningful shift of PCL crystallization exotherm to higher temperature in a 70/30 wt% PVDF/PCL blend [34].…”
Section: Figurementioning
confidence: 99%
“…It is worth noting that heterogeneous nucleation in immiscible blends can occur both at molten surfaces (when the adjacent phase is still in the melt state) [14][15]43 and solid surfaces (when the crystallizing polymer is in contact with a previously crystallized component). 16,18,59 3.5 | Crystallization of the minor phase in immiscible ternary blends with partial-wetting morphology Virgilio et al 60 reported that droplets of the minor components in immiscible ternary blends with partial-wetting morphology form a perfectly segregated close-packed array at the interface of the cocontinuous morphology made by the other two major components.…”
Section: Crystallization Of the Major Phases In Immiscible Ternary mentioning
confidence: 99%
“…Interface-induced (or interface-assisted) nucleation has been previously reported in blends of crystalline/crystalline or crystalline/ amorphous components . [12][13][14][15][16][17][18] The nucleation phenomenon can be easily visualized by polarized optical microscopy (PLOM) and it has been attributed to different mechanisms such as the existence of an epitaxial relationship between the structures of the crystalline components 12 ; reduction of the energy barrier needed for nuclei formation due to phase separation [19][20][21][22][23] ; shear and "fluctuation-induced" nucleation, which promote some local chain orientation at the interface 15 ; chemical and/or physical interaction between the functional groups of polymer chains at the interface during melt processing 22,24 ; and local miscibility between the phase components. 13,[25][26][27][28] On the other hand, some studies attributed the observed surface-induced nucleation to the migration of impurities and heterogeneities to the interface between phases during the mixing stage.…”
mentioning
confidence: 99%